Management of Teacher Performance Improvement in Realizing Professional Teachers - Saepulloh, Saepulloh; Sauri, Sofyan; Suhendraya Muchtar, Hendi; Hanafiah, Hanafiah (Lafadz Jaya Publisher, 2022)
This study examined the management of teacher performance improvement in manifesting professional teachers in schools (Madrasah). The researcher conducted this study because of being motivated by the implementation of teacher performance management that has not been running optimally, especially in MAN 2 Majalengka and MAS Daarul Uluum PUI Majalengka. The sample in this study was the staff management of the schools, especially the principal, and teacher or educator staff in both schools studied, and the students, both at MAN 2 Majalengka and MAS Daarul Uluum PUI Majalengka. Then, the research method used in this study was descriptive-holistic aiming at finding out descriptive and holistic explanations as well as examining the assumptions used in more depth based on the findings and interpretations of the data in the research field. The data were collected through documentation techniques, interviews, and direct observation by the researcher. The results showed that the management of teacher performance improvement was able to make teachers professional, when the management of improving teacher performance was carried out based on the principles of scientific management and adjusted to the needs and characteristics of the school. Both schools (Madrasah) have been quite successful in implementing teacher performance management optimally. It could be seen in the efforts of both schools in several aspects examined. The planning aspects of both schools (Madrasah) involved a contextual analysis of all school resources and the school’s goals. The implementation of the aspects, in both schools (Madrasah), involved various performance indicators such as; (1) providing the guidance and distributing teacher self-evaluation tools; (2) carrying out academic supervision; (3) studying and concluding the results of academic supervision; (4) communicating the results of academic supervision to the teachers individually; (5) discussed the follow-up including; (a) conducting a non-formal program covering of handling cases that were individual and casuistic in nature (curative); (b) conducting a formal program, namely handling cases that were general in nature, and carried out by all teachers through training in the form of developing and deepening performance points such as composing a lesson plan. Both schools (Madrasah) showed their uniqueness, especially in the indicators of problem solving and following up. The evaluation aspects of both schools (Madrasah) were quite good at measuring existing education services, as well as measuring the extent to which the school elements have achieved predetermined qualifications. In general, this study concluded that both schools (Madrasah) were quite optimal in implementing teacher performance management by referring to the functional aspects of management; planning, implementation, and evaluation.